Neurological and psychiatric adverse effects of long-term methylphenidate treatment in ADHD: a map of the current evidence - Krinzinger, Helga; Hall, Charlotte L; Groom, Madeleine J; Ansari, Mohammed T; Banaschewski, Tobias; Buitelaar, Jan K; Carucci, Sara; Coghill, David; Danckaerts, Marina; Dittmann, Ralf; Falissard, Bruno; Garas, Peter; et al. (Neuroscience & biobehavioral reviews, 2019)
Methylphenidate (MPH), the most common medication for children with Attention Deficit/Hyperactivity Disorder (ADHD) in many countries, is often prescribed for long periods of time. Any long-term psychotropic treatment in childhood raises concerns about possible adverse neurological and psychiatric outcomes. We aimed to map current evidence regarding neurological and psychiatric outcomes, adverse or beneficial, of long-term MPH (> 1year) treatment in ADHD. We coded studies using a “traffic light” system: Green: safe/favours MPH; Amber: warrants caution; Red: not safe/not well-tolerated. Un-categorisable study findings were coded as “Unclear”. Although some evidence suggests an elevated risk of psychosis and tics, case reports describe remission on discontinuation. Several studies suggest that long-term MPH may reduce depression and suicide in ADHD. Evidence suggests caution in specific groups including pre-school children, those with tics, and adolescents at risk for substance misuse. We identified a need for more studies that make use of large longitudinal databases, focus on specific neuropsychiatric outcomes, and compare outcomes from long-term MPH treatment with outcomes following shorter or no pharmacological intervention.
Gesehen am 18.03.2020